Circ_0006220 (circ-TADA2A) accelerates prostate cancer cell malignant behaviors through miR-520f-3p/CDCA7 axis: Circ_0006220/miR-520f-3p/CDCA7 axis in PCa - Wan, Zijin; Liu, Gang (Cellular and Molecular Biology, 2024)
Prostate cancer (PCa) belongs to a prevailing neoplasm globally. Circular RNAs (circRNAs) are critical regulators in various tumors, but the role of circRNAs in PCa is obscure. In this research, a circRNA derived from the TADA2A gene (hsa_circ_0006220) was high-expressed in PCa tissues along with cell lines. Elevated Circ-0006220 expression was also related to PCa poor prognosis. Besides, circ-0006220 accelerated PCa cells malignant behaviors in vitro; it also promoted PCa tumor growth together with metastasis in vivo. Moreover, circ-0006220 competed with the Cell Division Cycle Associated 7 (CDCA7) for binding to miR-520f-3p. Circ-0006220 sponged miR-520f-3p to regulate CDCA7 expression, thereby promoting PCa cell proliferation, migration, invasion, along with metastasis. All above data suggested that circ-0006220 may be a worthy target for PCa therapeutics.